49. RESEARCH ON THE IMPACT OF SOCIAL NETWORKS ON CUSTOMER TRUST IN THE PHARMACY CHAIN SYSTEM IN CAN THO CITY IN 2024-2025 (Vietnam Journal of Community Medicine, 2025)
Objectives: Evaluate the impact scale and related factors of social networks on customer trust in pharmacy chains in Can Tho city in 2024-2025.Objects and methods: Cross-sectional descriptive study on 425 survey samples from social network users using systematic sampling method.Results: The results of the SEM model processing through the regression coefficient (estimate) show that information quality (0.263, p < 0.01) has the strongest positive impact on trust, followed by usefulness (0.172, p < 0.01) and interaction (0.162, p < 0.01). Perception of risk has no significant impact on trust (0.013, p = 0.815 > 0.05).Conclusion: Strengthening social media strategy can enhance customer trust and loyalty towards pharmacy chain system.
Keywords: Social networks; impact on customers; trust; pharmacy chain system